2021
DOI: 10.3390/ijms222313122
|View full text |Cite
|
Sign up to set email alerts
|

PHA-680626 Is an Effective Inhibitor of the Interaction between Aurora-A and N-Myc

Abstract: Neuroblastoma is a severe childhood disease, accounting for ~10% of all infant cancers. The amplification of the MYCN gene, coding for the N-Myc transcription factor, is an essential marker correlated with tumor progression and poor prognosis. In neuroblastoma cells, the mitotic kinase Aurora-A (AURKA), also frequently overexpressed in cancer, prevents N-Myc degradation by directly binding to a highly conserved N-Myc region. As a result, elevated levels of N-Myc are observed. During recent years, it has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In general, this study demonstrated the ferroptosis-related gene signatures in NB associated with the prognosis and proposed the possibility of the AURKA gene as a prognostic marker in NB, which is consistent with many preclinical studies (Berwanger et al, 2002;Otto et al, 2009;Ramani et al, 2015;Xie et al, 2017;Boi et al, 2021;Roeschert et al, 2021;Nguyen et al, 2022). We call for more attention to AURKA, expecting to open up a new way to treat NB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, this study demonstrated the ferroptosis-related gene signatures in NB associated with the prognosis and proposed the possibility of the AURKA gene as a prognostic marker in NB, which is consistent with many preclinical studies (Berwanger et al, 2002;Otto et al, 2009;Ramani et al, 2015;Xie et al, 2017;Boi et al, 2021;Roeschert et al, 2021;Nguyen et al, 2022). We call for more attention to AURKA, expecting to open up a new way to treat NB.…”
Section: Discussionsupporting
confidence: 90%
“…Previous microarray analyses showed that MYCN-amplified NBs had higher levels of AURKA mRNA than nonamplified NBs ( Berwanger et al, 2002 ) and this was confirmed in another study ( Otto et al, 2009 ), which showed that AURKA was not only required for the growth of MYCN-amplified NB cells but also for cells lacking amplified MYCN, which is consistent with the study of Roeschert et al (2021 ). In addition, it has been reported that changing the conformation of the AURKA activation loop with small molecules can effectively disrupt the AURKA /N-myc interaction in NB cancer cells ( Boi et al, 2021 ), and using selinexor and the AURKA inhibitor alisertib to synergistically increase the cytotoxicity of p53-mediated high-risk NB has potential therapeutic benefits ( Nguyen et al, 2022 ). As a result, we believe that AURKA may open up new avenues for biomarkers used in the prognosis of NB.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note the recurring phenomenon in which transcription of AURKA is regulated by some factors that AURKA engages with in protein-protein interactions, such as p53 [86], HIF1 [87], EGFR [88], Myc and FOXM1 [7] (figure 1). This suggests the presence of uncharted regulatory feedback loops, the exploration of which may reveal integrative circuits that control critical cellular functions, in addition to being exploited for therapeutic purposes [89,90].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…The poor prognosis of cancer patients is related to the over-expression of AURKA. Thus, AURKA is regarded as a target for cancer treatment [ 41 , 42 ]. The development of AURKA inhibitors has become a major challenge in cancer treatment [ 43 ].…”
Section: Discussionmentioning
confidence: 99%